Globally Harmonized System of Classification and Labelling of Chemicals (GHS) - United Nations (United Nations, 2017)
The Globally Harmonized System of Classification and Labelling of Chemicals (GHS) addresses classification and labelling of chemicals by types of hazards. It provides the basis for worldwide harmonization of rules and regulations on chemicals and aims at enhancing the protection of human health and the environment during their handling, transport and use by ensuring that the information about their physical, health and environmental hazards is available. The seventh revised edition of the GHS which includes, inter alia, revised criteria for categorisation of flammable gases within Category 1; miscellaneous amendments intended to clarify the definitions of some health hazard classes; additional guidance to extend the coverage of section 14 of the Safety Data Sheets to all bulk cargoes, regardless of their physical state, transported under IMO instruments;